Perekonomian pada Masa Nabi Muhammad Saw: ditinjau dari Kebijakan Fiskal - Ichsan, Atikah Nurul; Despileny, Iren; Jannah, Nisa Zahratul; A, Alpizar; H, Herlinda (Pacsasarjana UIN Sultan Syarif Kasim Riau, 2024)
his research aims to learn about the economics of the time of the Prophet Muhammad SAW which is reviewed from fiscal policy. The study uses the library research approach as a method of gathering data by involving an understanding and study of the theories that exist in various relevant literary sources. The economy of the Prophet Muhammad began after his Hijrah to Medina with the establishment of Medina as a peaceful and civilized country according to the principles of economic Shariah. The principle of fiscal policy in Islam aims to develop a society based on a balanced distribution of wealth by placing material and spiritual values on an equal and balanced level. During the time of the Prophet Muhammad SAW, the income of the state was derived from primary and secondary sources of income. This source of income is collected first and then spent according to the needs of the country. The status of the property belongs to the state and not to individuals. The place where the funds are gathered is called Baitul Mal using the balance-of-budget basis, which means that all receipts are spent on state expenditure. Thus the Prophet laid the foundations of fiscal wisdom based on justice since the time of Islamic rule.Keywords : Islamic Economy, Fiscal Policy, Prophet Muhammad SAW